Acceptability of a Telehealth Smoking Harm Reduction Intervention Using E-cigarettes Among Cigarette Smokers With Opioid Use Disorder: A Qualitative Analysis - El-Shahawy, Omar; Fawole, Adetayo; Kang, Brian; Abbasi-Kangevari, Mohsen; Braga, Mariana; Hamade, Nada; Doucoure, Mohamed; Cantrell, Jennifer; Sherman, Scott; Shpiegel, Svetlana; Schatz, Daniel; Stevens, Elizabeth R (Substance use : research and treatment, 2025)
Electronic cigarettes (EC) may serve as a potential smoking harm reduction tool by addressing both nicotine and behavioral dependence. This qualitative study reports the feasibility and acceptability of using EC and telehealth counseling among individuals in treatment programs for opioid use disorders (OUD) who smoke combustible cigarette, and was conducted as part of a randomized controlled trial. We report findings among participants in the EC arm. Qualitative interviews were conducted from March to May 2021. The interviews were audio recorded, transcribed, and de-identified. An inductive approach guided by the Theoretical Framework of Acceptability was used. We developed and refined a codebook through a collaborative iterative process and team discussions. Five analysts coded the transcripts using Quirkos, with independent double coding for each transcript to achieve consensus and ensure inter-coder reliability. In-depth thematic analysis was conducted via synthesizing relevant codes that were described and exemplified using representative quotes. Saturation was achieved when no additional codes emerged. Eleven participants randomized to EC were interviewed: average age = 55 years (range = 39-69), 88% were male, 41% non-Hispanic black, and 35% non-Hispanic white. Four main themes identified included inciting sense of accountability toward cigarette smoking reduction; acknowledging the value of telehealth counseling; noting positive attributes such as addressing craving, as well as challenges in utilizing EC such as the need to remember charging the EC; and finally, participants' expression of the satisfaction with their perceived improvements in their health and other behavioral aspects. The intervention combining telehealth counseling with EC was perceived as acceptable and helpful for reducing cigarette smoking, as well as resulting in other positive health benefits. ECs were easy to use and seemed to address craving; albeit with some challenges that can be addressed in future trials. EC combined with telehealth counseling carries great promise in smoking reduction among individuals with OUD.